Consecuencias materno-fetales del dengue en el primer trimestre en gestantes ingresadas al Hospital General León Becerra Camacho durante el periodo noviembre 2023-abril 2024. - Cerezo Santillán, Cinthya Paola (2024)
Dengue, a mosquito-transmitted viral disease, represents a significant risk to maternal-fetal health during pregnancy. This study investigates the consequences of dengue in the first trimester of pregnancy in women admitted to the León Becerra Camacho General Hospital between November 2023 and April 2024. An exhaustive review of medical records was carried out to identify maternal-fetal complications associated with the infection. . The findings indicate that dengue during the first trimester can lead to various complications, with the impact varying depending on individual factors. The conclusions highlight the importance of rigorous monitoring and implementation of preventive measures in endemic areas to reduce associated risks.